2015
DOI: 10.1158/1535-7163.mct-15-0185
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine Kinase-1 Protects Multiple Myeloma from Apoptosis Driven by Cancer-Specific Inhibition of RTKs

Abstract: Activation of acid sphingomyelinase (ASM) leads to ceramide accumulation and induces apoptotic cell death in cancer cells. In the present study, we demonstrate that the activation of ASM by targeting cancer-overexpressed 67-kDa laminin receptors (67LR) induces lipid raft disruption and inhibits receptor tyrosine kinase (RTK) activation in multiple myeloma cells. Sphingosine kinase 1 (SphK1), a negative regulator of ceramide accumulation with antiapoptotic effects, was markedly elevated in multiple myeloma cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 48 publications
1
29
0
Order By: Relevance
“…Furthermore, the present results indicated that the cytotoxic effects of chemotherapeutic drugs on TC cells were promoted by siRNA-mediated knockdown or pharmacological inhibition of SPHK1 in vitro. A previous study indicated that inhibition of SPHK1 activity by treatment with safingol markedly potentiated epigallocatechin gallate-induced apoptotic activity in vitro and in vivo (32). The results of the present study were consistent with several studies on other cancer types (33)(34)(35).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, the present results indicated that the cytotoxic effects of chemotherapeutic drugs on TC cells were promoted by siRNA-mediated knockdown or pharmacological inhibition of SPHK1 in vitro. A previous study indicated that inhibition of SPHK1 activity by treatment with safingol markedly potentiated epigallocatechin gallate-induced apoptotic activity in vitro and in vivo (32). The results of the present study were consistent with several studies on other cancer types (33)(34)(35).…”
Section: Discussionsupporting
confidence: 92%
“…It has been confirmed to be involved in regulating various physiological functions such as platelet aggregation, neurotransmission, and vascular smooth muscle regulation ( Saravani et al, 2012 ). Besides, studies reported that cGMP was crucial in cell proliferation, differentiation, and apoptosis ( Tsukamoto et al, 2015 ; Huang Y. et al, 2017 ). Particularly, cGMP was confirmed to be an important signaling molecule downstream of 67LR.…”
Section: Discussionmentioning
confidence: 99%
“…The best response was stable disease in 6/37 (16%) for an average of 3.3 months (range 1.8-7.2 months). Safingol synergistically sensitized epigallocatechin-induced apoptotic cell death, and suppressed multiple myeloma cells by preventing protein tyrosine kinase phoshorylation and activation of death-associated protein kinase 1 (DAPK1) [151]. As high SphK1 correlates with resistance to cisplatin in gastric cancer, safingol was used synergistically with cisplatin to restore the efficacy of the chemotherapy in gastric cancer cells [152].…”
Section: Safingolmentioning
confidence: 99%